TRACKING OF SYMPTOMS OF DEPRESSION, ANXIETY AND STRESS IN PHYSIOTHERAPEUTS DURING THE COVID PANDEMIC 19. (Movimenta (ISSN 1984-4298), 2021)
Objective: Track symptoms of anxiety, depression and stress in physical therapists at a public hospital in Goiás. Methods: This is an observational, cross-sectional and quantitative study, with physiotherapists who have been competing for at least 6 months. To assess symptoms of anxiety, depression and stress, the Depression, Anxiety and Stress scale (DASS-21) was used, in addition to a socioeconomic questionnaire. Continuous variables were presented as mean and standard deviation, while categorical variables were presented in absolute and relative frequency. Results: There was a higher prevalence of female physiotherapists (73.5%), stress had a higher prevalence among physiotherapists, with symptoms from mild to extremely severe in 45% of them, however, anxiety showed a higher frequency of moderate symptoms (15% ), followed by extremely severe (12%) and severe (3%). Conclusion: Physiotherapists working in a public hospital had a higher prevalence of symptoms of stress and anxiety, with depression having the lowest prevalence among them. Serving as an alert for the mental health care of these professionals.
Keywords: PHYSICAL THERAPISTS; STRESS PHYCHOLOGICAL; ANXIETY; DEPRESSION; HEALTH PERSONNEL